PERBEDAAN pH SALIVA SEBELUM DAN SESUDAH MENGUNYAH BUAH PISANG BARANGAN (MUSA ACUMINATA COLLA) PADA SISWA KELAS VIII SMPN 2 KARANG INTAN KABUPATEN BANJAR - hartati, irma; said, fahmi; nurwati, bunga (Poltekkes Kemenkes Banjarmasin, 2022)
Saliva is a complex oral fluid that is a combination of various fluids andcomponents that are excreted into the mouth. Barangan banana (Musa AcuminataColla) is a fruit with fermented carbohydrates that can increase acid production bybacteria in the oral cavity so that the oral cavity becomes acidic. This situation causesdemineralization of the tooth surface so that the caries formation process can occur.The purpose of this study was to determine differences in salivary pH before andafter chewing barangan bananas in class VIII students of SMPN 2 Karang Intan, BanjarRegency. The subjects of this study were 60 people taken by the Total Samplingmethod with the design of one group pretest posttest. Saliva was taken by spittingmethod which was done before and after chewing barangan banana.The results showed that the average before chewing bananas was 6.54 and theaverage after chewing bananas was 6.47. The results of statistical analysis by PairedSample T-test obtained a mean of 0.075, with p value = 0.004, so that it was smallerthan alpha α = 0.05 or (p = 0.004 <α = 0.05).The conclusion of this study is that there are differences in salivary pH beforeand after chewing barangan bananas (Musa Acuminata Cola). It is recommended toeat fruits, one of which is a good barangan banana to normalize salivary pH.